Econometrics - Creel, Michael (Barcelona, 2012)
This document integrates lecture notes for a one year graduate level course with computer programs that illustrate and apply the methods that are studied. The immediate availability of executable (and modi able) example programs when using the PDF1 version of the document is one of the advantages of the system that has been used. On the other hand, when viewed in printed form, the document is a somewhat terse approximation to a textbook. These notes are not intended to be a perfect substitute for a printed textbook. If you are a student of mine, please note that last sentence carefully. There are many good textbooks available. A few of my favorites are listed in the bibliography.